Simple cryopreservation protocol for Luffa pollen: enhancing breeding efficiency - Nagar, Arvind; Gowthami, Ravi; Sureja, Amish Kumar; Munshi, Anilabha Das; Verma, Manjusha; Singh, Awani Kumar; Mallick, Niharika; Singh, Jogendra; Chander, Subhash; Shankar, Muthusamy; Pathania, Pooja; Rajkumar, Subramani (Frontiers in Plant Science, 2023)
This study aimed to develop a long-term pollen storage protocol for Luffa species (L. acutangula, L. cylindrica, L. echinata, and L. graveolens) and assess its potential for crop improvement. The optimal medium for in vitro pollen germination varied by species, with Brewbaker and Kwack medium with 10% sucrose suitable for L. acutangula, L. cylindrica, and L. echinata, and BK medium with 3% sucrose ideal for L. graveolens. Overestimation in staining tests compared to in vitro pollen germination was observed. The best results for cryopreservation were achieved with desiccation periods of 20, 30, and 40 minutes, maintaining moisture content between 14.04% and 18.55%. Pollen viability was negatively correlated with storage temperature (25, 4, and -20 °C) and duration. Cryopreserved pollen at -196 °C exhibited the highest viability over a prolonged period (2 months) and was comparable to fresh pollen in terms of germination, ovule fertilization, fruit and seed set. This study presents a simple and reproducible pollen cryopreservation protocol applicable across Luffa species, facilitating long-term storage and its use in crop improvement efforts.